Tropical and subtropical Asia's valued tree species under threat. Issue 3 (14th February 2022) - Gaisberger, Hannes; Fremout, Tobias; Kettle, Chris J.; Vinceti, Barbara; Kemalasari, Della; Kanchanarak, Tania; Thomas, Evert; Serra‐Diaz, Josep M.; Svenning, Jens‐Christian; Slik, Ferry; Eiadthong, Wichan; Palanisamy, Kandasamy; et al.
Abstract: Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration. Abstract : Article impact statement : There are specific forest areas and degraded lands in Indonesia and Malaysia that are hotspots for tree species conservation and restoration. Abstract : Especies de Árboles Valoradas y Amenazadas de Asia Tropical y Subtropical Resumen: La diversidad de árboles en los bosques tropicales y subtropicales de Asia es un eje central para las soluciones basadas en la naturaleza. La vulnerabilidad de las especies ante las múltiples amenazas, las cuales afectan el suministro de servicios ambientales, es un tema poco comprendido. Realizamos una evaluación regional espacialmente explícita de la vulnerabilidad de 63 especies de árboles de importancia socioeconómica ante la sobreexplotación, incendios, sobrepastoreo, conversión del hábitat y cambio climático. Los árboles se seleccionaron para su evaluación a partir de listas nacionales de prioridades, y las selecciones fueron validadas por una red de expertos de 20 países. Usamos el modelado de idoneidad Maxent para predecir el rango de distribución de las especies, conjuntos de datos espaciales de libre acceso para mapear la exposición a las amenazas y rasgos funcionales para estimar la susceptibilidad a las amenazas. Con base en la vulnerabilidad a las amenazas actuales y al cambio climático, identificamos las áreas prioritarias para su conservación y restauración. En general, el 74% de las áreas más importantes para la conservación de estos árboles quedó fuera de las áreas protegidas y todas las especies estaban seriamente amenazadas en promedio en el 47% de su distribución nativa. Las amenazas más inminentes fueron la sobreexplotación y la conversión del hábitat; las poblaciones estuvieron seriamente amenazadas por estos factores en promedio en el 24% y 16% de su distribución, respectivamente. Nuestro modelo predijo un impacto general limitado del cambio climático, aunque algunas especies estudiadas tuvieron la probabilidad de perder más del 15% de su hábitat para el 2050 debido a este factor. Identificamos áreas naturales específicas en las selvas de Borneo como puntos calientes para la conservación in situ de los recursos genéticos forestales, más del 82% de los cuales estaban fuera de las áreas protegidas designadas. También identificamos áreas degradadas en los Ghats Occidentales, los bosques secos de Indochina y las selvas de Sumatra como puntos calientes para la restauración, en donde la siembra o la regeneración natural asistida ayudarán a conservar estas especies. Además, identificamos campos de cultivo al sur de India y Tailandia como potenciales opciones importantes de agrosilvicultura. Nuestros resultados resaltan la necesidad de acciones regionales coordinadas para la conservación y restauración efectivas. 亚洲热带及亚热带地区有价值的树种面临威胁: 【摘要】 保护亚洲热带和亚热带森林的树木多样性是基于自然的解决方案的关注重点。物种面对多种威胁的脆弱性会影响生态系统服务的供给, 但目前人们对此仍知之甚少。我们对63种具有社会经济意义的树种面对过度开发、火灾、过度放牧、栖息地转换和气候变化的脆弱性进行了全区域空间显式评估。我们进行评估的树种来自国家优先保护名录, 树种的选择得到代表 20个国家的专家网络的认可。研究使用Maxent适宜性模型预测了物种分布范围, 并用可获取的空间数据集绘制了威胁暴露情况, 用功能特征估计了威胁敏感性。我们利用暴露地图和敏感性估计结果得到了物种特异的脆弱性地图, 并根据物种对当前威胁和气候变化的脆弱性, 确定了保护和恢复的优先区域。总的来说, 对这些树种的保护最重要的区域有 74%在保护区之外, 所有树种平均在其原生分布区 47%的范围内受到严重威胁。最紧迫的威胁是过度开发和栖息地转换;树木种群平均在其 24%和16%的范围内受到这些因素的严重威胁。我们的模型预测得到的气候变化整体影响有限, 尽管一些物种到2050年可能会因气候变化而失去超过15%的栖息地。我们发现婆罗洲雨林中特定的自然区域应作为森林遗传资源原地保护的热点地区, 该区域82%以上的面积位于已有保护区之外。我们还确定了西高止山、中南半岛旱林和苏门答腊雨林的退化地区为恢复热点地区, 在这些地区种植树木或辅助自然再生将有助于保护树种, 而印度南部和泰国的耕地则是潜在的重要农林地。我们的结果强调了为有效保护和恢复而采取区域性协调行动的必要性。【翻译: 胡怡思;审校: 聂永刚】